How kinship and marriage customs influence nutritional outcomes among males and females - Elza S. Elmira; Bezawit Beyene Chichaibelu; Matin Qaim (University of Bonn, Center for Development Research (ZEF), 2024)
Malnutrition in its various forms is a serious problem in many countries, contributing to human suffering, large healthcare costs, and hampered economic and human development. While various policies to reduce malnutrition exist, such policies typically fail to consider cultural factors. Here, we contribute to the scant literature on cultural practices and nutrition, focusing on issues of gender discrimination and intra-household resource allocation. In particular, using representative panel data from Indonesia covering a period of 22 years, we analyze how ethnic-based kinship systems and marriage customs influence the nutritional status of male and female individuals. We find that patrilocal practices contribute to a higher body mass index (BMI) among males, in comparison to both males in other cultural settings and females. Matrilocality contributes to a higher BMI among females in comparison to females in other cultural settings but not in comparison to males. Bride price practices increase BMI among both male and female individuals. Quantile regressions show that the effects on increasing BMI are especially pronounced among those already overweight, whereas discrimination against females is particularly pronounced among the underweight. Our findings underline that cultural practices matter for nutritional outcomes. Better understanding the links in different cultural settings is important for effective nutrition policies, especially given the fact that different malnutrition problems coexist in many countries.
Keywords: I10; J15; J16; Z13; 330; obesity; kinship; bride price; patrilocality; matrilocality; Indonesia